PENGEMBANGAN KOMPETENSI SIKAP DALAM PEMBELAJARAN MATEMATIKA SECARA HOLISTIK BERSUMBER QUR’AN - Hartoyo, Agung; Nursangaji, Asep; Suratman, Dede (Universitas Tanjungpura, 2019)
AbstractThis study aims to describe the process of developing spiritual and social attitudes competencies, in a holistic learning of mathematics sourced in the Qur'an. Qualitative research is applied in the preparation of teaching materials based on the integration of core competencies of revised Curriculum-13, and the development of attitude competencies in mathematics learning based on the Qur'anic. The subjects of the study were SMP / MTs students in the lessons of Straight Line Equation. The research data includes documents, learning recordings, and interviews, and it’s analyzed using the Miles & Huberman Method. The study resulted in: (1) mathematics teaching materials on the topic of the Straight Line Equations sourced of the Qur'anic (al Anfal) verses 65-66, to teach holistically, (2) The process of developing competency attitudes is carried out as long as the learning takes place from introduction to closing the lesson. In developing a spiritual attitude, two students are assigned to read the verses of the Qur’an and their translations, then discuss the content of mathematics. Students are aroused by curiosity with questions about verse, working collaboratively with friends, choosing the best ideas (tolerant), and being responsible for completing tasks. In developing skills and knowledge competencies, students are guided to achieve the process of modeling problems related to the Qur'anic verses, so that they find problem solving procedures, or mathematical concepts from the topics studied.Keywords: attitude competency development, holistic mathematics learning.